Implementation of the International Health Regulations (2005) Through Cooperative Bioengagement - Standley, Claire J.; Sorrell, Erin M.; Kornblet, Sarah; Fischer, Julie E.; Katz, Rebecca (Frontiers in Public Health, 2015)
Cooperative bioengagement efforts, as practiced by U.S. government-funded entities, such as the Defense Threat Reduction Agency’s Cooperative Biological Engagement Program, the State Department’s Biosecurity Engagement Program, and parallel programs in other countries, exist at the nexus between public health and security. These programs have an explicit emphasis on developing projects that address the priorities of the partner country as well as the donor. While the objectives of cooperative bioengagement programs focus on reducing the potential for accidental or intentional misuse and/or release of dangerous biological agents, many partner countries are interested in bioengagement as a means to improve basic public health capacities. This article examines the extent to which cooperative bioengagement projects address public health capacity building under the revised International Health Regulations and alignment with the Global Health Security Agenda action packages.